UV fluences required for compliance with ballast water discharge standards using two approved methods for algal viability assessment. (October 2018) - Lundgreen, Kim; Holbech, Henrik; Pedersen, Knud Ladegaard; Petersen, Gitte Ingelise; Andreasen, Rune Røjgaard; George, Christaline; Drillet, Guillaume; Andersen, Martin
Abstract: This study investigates the extra UV fluence needed to meet the International Maritime Organisation's ballast water discharge standards for the 10–50 μm size-class using the approved vital stain (VS) method compared to the Most Probable Number (MPN) method for organism viability assessment. Low- and medium pressure UV collimated beam treatments were applied to natural algae collected in temperate and tropical water environments and analysed using both methods. About 10 times higher UV fluence was required to meet discharge standards when using VS compared to MPN. Implementing a dark-hold period after UV treatments decreased algal viability. Length of dark-hold period to meet discharge standards decreased with increasing UV fluence. No significant differences between temperate and tropical samples were observed. The results showed that UV treated algae assessed using the VS method could meet discharge standards by increasing fluence and/or introducing a dark-hold period. Highlights: Compliance achieved with vital stain by increasing UV fluence 10–15 times Compliance achieved with vital stain by introducing dark hold periods Algae <10 μm need more attention as they potentially hold high invasive potential.